Stimulation of in vitro transcription from heterologous promoters by the simian virus 40 enhancer. - Sassone-Corsi, P (1984)
Insertion of the simian virus 40 enhancer upstream from the +33 to -34 adenovirus major late promoter element or the +62 to -102 conalbumin promoter region causes a 10-fold stimulation of specific transcription using a whole cell extract but not an S100 extract. Many of the in vivo effects of the enhancer were mimicked in vitro. This stimulation occurred only in cis, with either orientation of the 72-base-pair repeat, and was markedly decreased by deletions known to diminish the enhancer activity in vivo. However, in vitro, the 72-base-pair repeat did not stimulate at a distance or in the presence of a strong upstream promoter element.